PROPOSTA DE EDUCAÇÃO ESCOLAR INDÍGENA PARA A COMUNIDADE OFAIÉ-XAVANTE: DESAFIOS E LIMITES - ANDRESSA LUIZA MONTANHA DE ARAUJO (2022)
This Master's research, linked to the Postgraduate Program in Education of the UFMS, Três Lagoas campus, Research Line Education, Childhood and Diversity, aims to analyze how the Ofaié Iniecheki school of the Ofaié-Xavante Indigenous Community offers education in structural and pedagogical aspects, as well as to understand the historical processes that allowed these conditions. As the indigenous people have a history of exclusion in the history of Brazil and still today, it was essential to verify if the Ofaié students have had their rights executed in practice. This work was carried out by means of bibliographic and documental research. The documental analysis was done through sources about the indigenous legislation during the colonial, imperial and republican periods, as well as the laws that assure the indigenous rights to a quality education. The documents "Political Pedagogical Project" and "Internal Rules", provided by the Ofaié Iniecheki school board, played a fundamental role in the analysis of this research. In the analysis of the research, through the framework created by reading the legislation and theoretical references and the comparative analysis of these documents with the PPP and the Internal Regulations, it was possible to understand if the basic principles of Indigenous School Education (Bilingualism, Interculturalism, Specificity, Differentiation and Autonomy) really make sense for Ofaié Iniecheki. And given the context in which it is inserted, it was concluded that the school does not correspond to the principles of Indigenous School Education, taking into account that indigenous knowledge is not prioritized by the Brazilian educational system and that this reality is directly related to the Ofaié village school.